2015
DOI: 10.1242/jcs.167452
|View full text |Cite
|
Sign up to set email alerts
|

Access of torsinA to the inner nuclear membrane is activity dependent and regulated in the endoplasmic reticulum

Abstract: TorsinA (also known as torsin-1A) is a membrane-embedded AAA+ ATPase that has an important role in the nuclear envelope lumen. However, most torsinA is localized in the peripheral endoplasmic reticulum (ER) lumen where it has a slow mobility that is incompatible with free equilibration between ER subdomains. We now find that nuclear-envelope-localized torsinA is present on the inner nuclear membrane (INM) and ask how torsinA reaches this subdomain. The ER system contains two transmembrane proteins, LAP1 and LU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 50 publications
(139 reference statements)
3
44
0
Order By: Relevance
“…Immunostained samples were quantitated in a blind fashion such that regions from the plasma membrane and nuclear membrane were selected by using transmitted light images and lamin B 2 images, respectively, and the ratio of nuclear membrane to the plasma membrane was compared between different constructs. Line scan analysis was performed by randomly drawing a horizontal line near the center of the nucleus followed by a vertical line perpendicular to the first (73). Fluorescence intensity was quantified along both lines using MetaMorph software.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostained samples were quantitated in a blind fashion such that regions from the plasma membrane and nuclear membrane were selected by using transmitted light images and lamin B 2 images, respectively, and the ratio of nuclear membrane to the plasma membrane was compared between different constructs. Line scan analysis was performed by randomly drawing a horizontal line near the center of the nucleus followed by a vertical line perpendicular to the first (73). Fluorescence intensity was quantified along both lines using MetaMorph software.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of LULL1 leads to a redistribution of TorsinA WT from the ER to the NE, but Walker A (K108A) and Walker B (E171Q) mutants as well as TorsinA lacking its hydrophobic domain are not affected (Vander Heyden et al, 2009, Goodchild et al, 2015). This suggests that LULL1 may play a role in regulating the subcellular distribution of TorsinA.…”
Section: Molecular Properties Of the Torsins And Their Membrane-spannmentioning
confidence: 99%
“…In fact, it has been previously shown that mutation of cysteines in TorsinA affects both nucleotide and cofactor binding (Zhu et al, 2008, Zhu et al, 2010). LAP1 forms a complex with TorsinA in vitro (Brown et al, 2014, Zhao et al, 2013) (Figure 5A), but in vivo conditions (or crosslinking in vitro ) are required to observe higher-order oligomers (Jungwirth et al, 2010, Vander Heyden et al, 2009, Li et al, 2014, Brown et al, 2014, Goodchild et al, 2015). The precise composition of these oligomers remains poorly understood.…”
Section: Molecular Mechanism Of Torsin Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…TorsinA is partitioned between the ER and the contiguous perinuclear space of the nuclear envelope, and its localization is controlled in part by its association with LAP1 and LULL1, type II transmembrane proteins residing in the nuclear envelope and ER, respectively (12)(13)(14). Another unusual property of Torsins is that they lack significant basal ATPase activity in isolation and are tightly regulated by LAP1 and LULL1, which integrate into the Torsin ring via AAA-like domains to trigger ATP hydrolysis through an active site complementation mechanism (15)(16)(17).…”
mentioning
confidence: 99%